Efficacy of short-chain polypeptide-based EEN formulas in alleviating intestinal injury in children with Crohn’s disease: a single-center study in China - Wu, Runqiu; Yang, Jin; Cao, Jinjin; Wang, Peng; Wang, Chenhui; Chen, Wenxin; Wu, Yanling; Zheng, Xinguo; Jin, Yu; Yang, Hui (Frontiers in Nutrition, 2023)
Short chain polypeptides are composed of 3-9 amino acids, which can be absorbed by the intestinal tract without digestive enzymes and ATP energy. Crohn's disease (CD) is a chronic non-specific disease derived from inflammation and damage of the gastrointestinal tract. To investigate the effect of short chain polypeptide-based exclusive enteral nutrition (EEN) formulas on intestinal injury in Chinese children with active CD. A total of 84 children with diagnosis of Crohn's disease (CD) in the Department of Pediatric Gastroenterology, Children's Hospital of Nanjing Medical University from January 2013 to January 2019, were divided into mild and moderate-to-severe active CD groups. Each group was further divided into two subgroups: drug groups and short chain polypeptide plus drug groups. Levels of intestinal fatty acid binding protein (I-FABP) in the blood, Fecal calprotectin (FC) and Occludin protein in the intestinal mucosa 1d before treatment and 2m after treatment, and endoscopic and histopathological observations were detected to compare the changes of intestinal injury in children with active CD. After 8 weeks of treatment, the SES-CD scores and Chiu scores of ileocecal area and terminal ileum of children with the mild active CD and ileocecal area of children with moderate-to-severe active CD in short chain polypeptide plus drug groups were significantly lower than those in the drug group. While the OD value of Occludin in the terminal ileum and ileocecal area of children with the mild active CD and ileocecal area of children with moderate to severe active CD after short chain polypeptide-based EEN formulas and drug treatment was significantly higher than those in drug group (p<0.05). Meanwhile, the levels of FC and I-FABP were significantly decreased (p<0.05). The results show that short chain polypeptide-based EEN formulas effectively alleviate intestinal injury in children with active CD.